2015
DOI: 10.1093/jhps/hnv079
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of hip arthroscopy in patients with mild to moderate osteoarthritis—A prospective study

Abstract: Osteoarthritis (OA) of the hip is a common cause of hip pain. The arthroscopic management of patients with femoro-acetabular impingement (FAI) has been reported to yield good outcomes. The purpose of this study was to report on outcome following the arthroscopic treatment of patients with FAI in the presence of mild to moderate OA. Seventy-five patients undergoing arthroscopic surgery for FAI, all with preoperative radiological signs of mild to moderate OA were prospectively included in this study. A 2-year fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
(26 reference statements)
0
27
0
Order By: Relevance
“…Surgical treatment for FAI syndrome aims to reproduce normal hip anatomy, thereby reducing pain and improving hip function. Several recent studies have reported good results following arthroscopic treatment for FAI syndrome at short-to mid-term follow-ups [5][6][7][8][9][10][11]. The results of arthroscopic surgery have been reported to be similar to those of open surgery, regarding both clinical outcome measurements and the conversion rate to total hip arthroplasty (THA), although hip arthroscopy results in a significantly higher general health-related quality of life [12], with fewer complications [13].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment for FAI syndrome aims to reproduce normal hip anatomy, thereby reducing pain and improving hip function. Several recent studies have reported good results following arthroscopic treatment for FAI syndrome at short-to mid-term follow-ups [5][6][7][8][9][10][11]. The results of arthroscopic surgery have been reported to be similar to those of open surgery, regarding both clinical outcome measurements and the conversion rate to total hip arthroplasty (THA), although hip arthroscopy results in a significantly higher general health-related quality of life [12], with fewer complications [13].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Having said that, there are several studies that show that patients with degenerative changes can still have good to excellent outcomes. 5,6 How do we make sense of these conflicting results?…”
Section: See Related Article On Page 2353mentioning
confidence: 99%
“…Scoring criteria: The clinical manifestations before and after treatment were scored in reference to visual analogue scale (VAS) [8][9][10][11] and the score of each symptom and total scores were calculated. According to the degree of each symptom, from the (1) Local itching: 0 for absence of itching, 1 for occasional itching, 2 for attack due to improper diet or overstrain, 3 for intermittent attack, 4 for frequent attack, 5 for severe itching and sleeping disturbance(2) Regarding red patches, blister, thickening of horny layer and scaly skin: 0 for absence of red patches/blister/thickening of horny layer/scaly skin; 1 for the lesion area of red patches/blister/thickening of horny layer/scaly skin less than or equal to 2 cm 2 , or reduced by ≥ 80% as compared with that before treatment; 2 for the lesion area of red patches/blister/thickening of horny layer/scaly skin larger than 2 cm 2 but less than or equal to 4 cm 2 , or reduced by ≥ 60% as compared with those before treatment; 3 for the lesion area of red patches/blister/thickening of horny layer/scaly skin larger than 4 cm 2 but less than or equal to 6 cm 2 or reduced by ≥ 40% as compared with those before treatment; 4 for the lesion area of red patches/blister/thickening of horny layer/scaly skin larger than 6 cm 2 but less than or equal to 8 cm 2 or reduced by ≥ 20% as compared with those before treatment; 5 for the lesion area of red patches/blister/ thickening of horny layer/scaly skin larger than 8 cm 2 or reduced by <10% as compared with those before treatment.…”
Section: Therapeutic Effect Indexmentioning
confidence: 99%